2020
DOI: 10.1371/journal.pone.0230299
|View full text |Cite|
|
Sign up to set email alerts
|

Engineering 3D perovskites for photon interconversion applications

Abstract: In this review, we highlight the current advancements in the field of triplet sensitization by three-dimensional (3D) perovskite nanocrystals and bulk films. First introduced in 2017, 3D perovskite sensitized upconversion (UC) is a young fast-evolving field due to the tunability of the underlying perovskite material. By tuning the perovskite bandgap, visible-to-ultraviolet, near-infrared-to-visible or green-to-blue UC has been realized, which depicts the broad applicability of this material. As this research f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 91 publications
(135 reference statements)
0
18
0
Order By: Relevance
“…[11] There are several distinct routes possible for creating higher energy photons, including non-linear frequency generation, UC based on the ladder-like energy levels in lanthanide ions [12][13][14] and triplet-triplet annihilation (TTA) in organic semiconductors. [15][16][17][18][19][20][21][22][23] In TTA, two spin-triplet states electroni-cally interact and 'annihilate' to generate a high-energy singlet state in a spin-allowed process. Due to the low absorption cross sections of triplet states, these states are 'dark' and only weakly accessible by optical means.…”
Section: Introductionmentioning
confidence: 99%
“…[11] There are several distinct routes possible for creating higher energy photons, including non-linear frequency generation, UC based on the ladder-like energy levels in lanthanide ions [12][13][14] and triplet-triplet annihilation (TTA) in organic semiconductors. [15][16][17][18][19][20][21][22][23] In TTA, two spin-triplet states electroni-cally interact and 'annihilate' to generate a high-energy singlet state in a spin-allowed process. Due to the low absorption cross sections of triplet states, these states are 'dark' and only weakly accessible by optical means.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, perovskite PV technologies have exploded in relevance, thanks in large part to the increase in efficiency from 3.8% to 25.5% 24,25 . Additionally, these materials have been studied in other applications including but not limited to light‐emitting diodes (LEDs), 26 lasers, 27–29 photodetectors, 30,31 triplet–triplet annihilation‐based upconversion (TTA‐UC), 32–35 catalysis, 36,37 and memory 38,39 …”
Section: Introductionmentioning
confidence: 99%
“…[ 1,6,7 ] This phenomenon was first discovered in single molecules of anthracene and phenanthrene as early as 1962, [ 8 ] continued research has produced increasingly efficient TTA‐UC systems and revealed the ease of tuning optical properties in multicomponent systems. [ 9–11 ] The first step in two‐component triplet upconversion is photon absorption by a sensitizer (donor) molecule, resulting in the generation of a singlet excited state, S 1 ( Figure a). It converts to the triplet excited state ( T 1 ) through intersystem crossing (ISC) and the excitation energy is then donated to an acceptor molecule through triplet energy transfer (TET).…”
Section: Introductionmentioning
confidence: 99%